2020
DOI: 10.1007/s00540-020-02856-x
|View full text |Cite
|
Sign up to set email alerts
|

Clotting functional stability of withdrawing blood in storage for acute normovolemic hemodilution: a pilot study

Abstract: Purpose This study was conducted to time-course changes of clotting function of withdrawing blood for acute normovolemic hemodilution (ANH). Methods Twelve enrolled patients who underwent ANH from August, 2018 to January, 2019. Blood was withdrawn into blood collection pack and shaken at 60–80 rpm for 24 h in room temperature. Clot formation was evaluated using rotational thromboelastometry (ROTEM™) just after blood withdrawal (control) and 4, 8, 12 and 24 h after blood withdrawal. We compared with the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Kinoshita et al reported that the clotting function of the withdrawing blood for ANH can be stable within eight hours at room temperature. 29 In contrast, Cardigan et al found that storing whole blood at ambient temperature can prolong aPTT within eight hours. 30 In this study, the anticoagulants in the storage bag might contribute to the hypocoagulation since PT and aPTT values prolonged further at T2 than T1.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kinoshita et al reported that the clotting function of the withdrawing blood for ANH can be stable within eight hours at room temperature. 29 In contrast, Cardigan et al found that storing whole blood at ambient temperature can prolong aPTT within eight hours. 30 In this study, the anticoagulants in the storage bag might contribute to the hypocoagulation since PT and aPTT values prolonged further at T2 than T1.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, whether the anticoagulants in the storage bag induce perioperative hypocoagulation still remained controversial. Kinoshita et al reported that the clotting function of the withdrawing blood for ANH can be stable within eight hours at room temperature 29 . In contrast, Cardigan et al found that storing whole blood at ambient temperature can prolong aPTT within eight hours 30 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Studies on cardiopulmonary bypass heart surgery have shown reduced platelet aggregation function in ANH-collected blood samples, although thrombin production remains unaffected. 21 While ANH-collected blood stored at room temperature for up to 8 hours has a hemostatic effect, 22 preserving it at 4 °C helps maintain platelet activity. 23 In our study, we used a 4 °C refrigerator to maximize blood clotting function preservation.…”
Section: Discussionmentioning
confidence: 99%